2020
DOI: 10.1002/adfm.202003556
|View full text |Cite
|
Sign up to set email alerts
|

Etching‐Doping Sedimentation Equilibrium Strategy: Accelerating Kinetics on Hollow Rh‐Doped CoFe‐Layered Double Hydroxides for Water Splitting

Abstract: Exploring highly active and inexpensive bifunctional electrocatalysts for water‐splitting is considered to be one of the prerequisites for developing hydrogen energy technology. Here, an efficient simultaneous etching‐doping sedimentation equilibrium (EDSE) strategy is proposed to design and prepare hollow Rh‐doped CoFe‐layered double hydroxides for overall water splitting. The elaborate electrocatalyst with optimized composition and typical hollow structure accelerates the electrochemical reactions, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 63 publications
6
77
0
Order By: Relevance
“…As shown in Figure 3a,b,2 DM OF-Fe/Co(1:2) had the lowest overpotential (238 mV) of 10 mA cm À2 ,t he lowest Tafel slope (52 mV dec À1 ), the largest C dl (66.9 mF cm 2 ), and the smallest R s (7.7 W)a nd R ct (3.3 W), as compared with MOF-Fe/Co(1:3), MOF-Fe/Co(1:1), MOF-Co, MOF-Fe, and RuO 2 (Supporting Information, Figures S8-S11). According to the experimental result, it is concluded that incorporation of Fe in MOF-Co could improve the conductivity and OER activity owing to the partial-charge transfer activation effect of Co. [1,19,31,32] Since the 2D MOF-Fe/Co(1:2) possessed the highest OER performance,i ti sn ecessary to understand the OER mechanism. After several CV cycling, there was asignificant change in the color of the 2D MOF-Fe/ Co(1:2) nanosheets,i.e., from orange to black (see the inset of Figure 3f).…”
Section: Nm By Afm (Figuresmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 3a,b,2 DM OF-Fe/Co(1:2) had the lowest overpotential (238 mV) of 10 mA cm À2 ,t he lowest Tafel slope (52 mV dec À1 ), the largest C dl (66.9 mF cm 2 ), and the smallest R s (7.7 W)a nd R ct (3.3 W), as compared with MOF-Fe/Co(1:3), MOF-Fe/Co(1:1), MOF-Co, MOF-Fe, and RuO 2 (Supporting Information, Figures S8-S11). According to the experimental result, it is concluded that incorporation of Fe in MOF-Co could improve the conductivity and OER activity owing to the partial-charge transfer activation effect of Co. [1,19,31,32] Since the 2D MOF-Fe/Co(1:2) possessed the highest OER performance,i ti sn ecessary to understand the OER mechanism. After several CV cycling, there was asignificant change in the color of the 2D MOF-Fe/ Co(1:2) nanosheets,i.e., from orange to black (see the inset of Figure 3f).…”
Section: Nm By Afm (Figuresmentioning
confidence: 99%
“…In recent years, cheap and efficient electrocatalysts based on non‐noble metals, especially transition‐metal (Ni, Co, Fe, etc.) compounds, have been widely studied for the oxygen evolution reaction (OER), owing to their elemental abundance in nature and low costs [1–4] . Metal–organic frameworks (MOFs) based on transition metal ions and organic ligands, having a well‐defined porous structure and a very large specific surface area, can endow them with multiple active sites in water oxidation (i.e., OER).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importation of precious metal ions into hydroxides can effectively regulate the intrinsic electronic structure, leading to optimize the OER property. [ 140–143 ] It is fairly easy to realize the target of importing precious metal ions through corrosion engineering. For example, Hao et al.…”
Section: Corrosion Engineering Enabled Electrocatalystsmentioning
confidence: 99%
“…In recent years, cheap and efficient electrocatalysts based on non‐noble metals, especially transition‐metal (Ni, Co, Fe, etc.) compounds, have been widely studied for the oxygen evolution reaction (OER), owing to their elemental abundance in nature and low costs [1–4] . Metal–organic frameworks (MOFs) based on transition metal ions and organic ligands, having a well‐defined porous structure and a very large specific surface area, can endow them with multiple active sites in water oxidation (i.e., OER).…”
Section: Introductionmentioning
confidence: 99%